Effects of drought stress on characteristics of water consumption and photosynthesis of the main shrub species in Lhasa semi-arid valley - XIN Fumei; JIA Liming; YANG Xiaolin; ZANG Jiancheng (浙江大学学报. 农业与生命科学版, 2016)
Vegetation restoration and reconstruction in Lhasa semi-arid valley is an important part of the Tibetan plateau national ecological security barrier construction. Water remains a major limiting factor in the area of vegetation restoration. Considering the climatic characteristics of the region, the less types of species and difficult to introduction, it is very important to carry out water research about native tree species and screen low-water drought-resistant species.This paper observed the water consumption and photosynthesis of the main shrub species in Lhasa semi-arid valley. The selected five species were Salix microstachya, Hippophae gyantsensis, Sabina pingii var. wilsonii, Sophora moorcroftiana and Buddleja minima. The water consumption (WC) and water consumption rate (WCR) of all seedlings under different drought stresses were measured by pot seedling mass method, and net photosynthetic rate (Pn), transpiration rate (Tr) and water use efficiency (WUE) of them were measured by an Li-6400 photosynthetic system.The results showed that: 1) With the intensification of drought stress, the WCs of Salix microstachya, H. gyantsensis and B. minima were all gradually declined. The WC of H. gyantsensis and B. minima had the steepest decline under light drought stress. Compared with the moderate drought stress, the WC of Salix microstachya under heavy drought stress was decreased by 71.8%. The WCs of Sabina pingii var. wilsonii and Sophora moorcroftiana were the largest under light drought stress. WC for each seedling was minimal under heavy drought stress. The day-and-night WCs of Sophora moorcroftiana and B. minima were only 208.3 g/m2 and 173.8 g/m2, respectively. 2) Under normal water supply, the WCRs of Salix microstachya, Sabina pingii var. wilsonii and B. minima were clearly bimodal curve. The peak of Salix microstachya appeared in 10:00-12:00 and 14:00-16:00, and those of Sabina pingii var. wilsonii and B. minima were in 12:00-14:00 and 16:00-18:00. The WCRs of H. gyantsensis and Sophora moorcroftiana were single-peak curve. The largest WCR of H. gyantsensis appeared in 12:00-14:00 and that of Sophora moorcroftiana was in 14:00-16:00. The WCRs of all species were single peak curve under light, moderate and heavy drought stress. But under light drought stress, the peaks of Sabina pingii var. wilsonii and B. minima appeared in 12:00-14:00, and the maximum values of WCRs of the other three species appeared in 14:00-16:00. The maximum WCR of each species was in 14:00-16:00 under moderate and heavy drought stress. 3) Under normal water supply, the Pn of Salix microstachya, H. gyantsensis and B. minima was significantly higher than that of Sabina pingii var. wilsonii, reached their maximum. The Pn of Sabina pingii var. wilsonii and Sophora moorcroftiana reached the maximum under light drought stress. With increased drought stress, the Tr of Salix microstachya, H. gyantsensis and B. minima was declined. The maximum Tr of Sabina pingii var. wilsonii and Sophora moorcroftiana appeared under light drought stress. Tr of each species had reached the minimum under heavy drought stress. 4) The WUEs of Sophora moorcroftiana under various water stress were significantly higher than that in other species. With increased drought stress, the WUE of B. minima was increasing. The WUE of Salix microstachya, H. gyantsensis and Sabina pingii var. wilsonii reached the maximum in light drought stress.